Unexpected Effect of Parvovirus B19 Infection on Hematological Parameters in Individuals with Normal Hemoglobin Variant - Al-Salait, Sadeq K.; Al-Atbee, Mohaned A.; Al-Hmudi, Hayder A. (Scientific Journal of Medical Research, 2021)
Objectives: To assess the effect of parvovirus B19 infection on blood counts, particularly hemoglobin, and reticulocyte count, in individuals with normal hemoglobin variants. Methods: study group, 100 individuals, is recruited from Basra Center for Hereditary Blood Diseases and Premarital Clinic in Al-Sader Teaching Hospital. Those individuals have normal hemoglobin HPLC and/or capillary electrophoresis. The samples are tested for parvovirus B19 using serological and molecular methods. Analysis of the data obtained was made by using SSPS software version SPSS 24. P-value less than 0.05 were considered statistically significant. Results: unexpectedly significant anemia is detected in as many as 34% of those who have parvovirus infection by PCR compared with those who do not. Serological studies, although they show good concordance with PCR results, are much less sensitive and may not be helpful in the detection of acute infection. The presence of specific IgG antibodies is not protective against re-infection or activation of an already existing one. Conclusion: Parvovirus B19 infection should be considered in any patient who has unexplained low Hb, even if he/she has a normal hemoglobin variant.